Transforming knowledge about anemia through interactive education for adolescent girls in madrasah - Ibrahim, Irviani Anwar; Damayati, Dwi Santy; Syarfaini, Syarfaini; Syahrir, Sukfitrianty; Adha, Andi Syamsiah; Alam, Syamsul (Sociality: Journal of Public Health Service, 2025)
Anemia is one of the common health problems worldwide, where there are around 1.62 billion people in the world suffering from anemia, or around 24.8% of the global population. This activity aims to provide education about anemia to adolescent girls at MTS Madani, Gowa Regency, through an interactive anemia literacy approach and health checks to detect anemia conditions early. This approach includes a series of structured stages, starting from pre-test, initial socialization, counseling, interactive discussion, health screening, to evaluation. The results obtained in the pre-test showed that 56.7% of respondents had sufficient knowledge about anemia, while in the post-test, this figure increased to 60.8%. Although there was a significant increase (P =0.000), a small percentage of respondents still had insufficient knowledge after attending the education, although the percentage was slightly lower in the post-test (39.2%) compared to the pre-test (43.3%). This suggests that the education provided can increase community literacy about anemia, but there is a need to continue to improve the quality and methods of counseling to achieve a more even level of understanding.